2023
DOI: 10.1111/hepr.13967
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of hepatitis E vaccination strategies among patients with chronic hepatitis B in China

Tingting Cui,
Xuefeng Zhang,
Qiang Wang
et al.

Abstract: AimThis study aimed to evaluate the cost‐effectiveness of hepatitis E vaccination strategies in the chronic hepatitis B (CHB) patients.MethodsBased on the societal perspective, cost‐effectiveness of three hepatitis E vaccination strategies: vaccination without screening, screening‐based vaccination, and no vaccination among CHB patients was evaluated using a decision tree‐Markov model, and incremental cost‐effectiveness ratios (ICERs) were calculated. Values for treatment costs and health utilities were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…A prospective study found that pregnant women infected with HEV have worse outcomes than those with acute viral hepatitis caused by other hepatitis viruses ( 5 ). In immunocompromised individuals and those with concomitant chronic hepatitis B infection, HEV infection often imposes a greater burden with a significantly longer course, higher economic burden, and greater resultant health loss ( 6 ). The prevention and control of hepatitis E (HE) is a major public health issue ( 7–10 ).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study found that pregnant women infected with HEV have worse outcomes than those with acute viral hepatitis caused by other hepatitis viruses ( 5 ). In immunocompromised individuals and those with concomitant chronic hepatitis B infection, HEV infection often imposes a greater burden with a significantly longer course, higher economic burden, and greater resultant health loss ( 6 ). The prevention and control of hepatitis E (HE) is a major public health issue ( 7–10 ).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In this issue of Hepatology Research, Cui et al evaluated the cost-effectiveness of hepatitis E vaccination strategies in Chinese patients with CHB. 19 Cost-effectiveness of three hepatitis E vaccination strategies: vaccination without screening, screening-based 122 -Hepatology Research. 2024;54:122-124. wileyonlinelibrary.com/journal/hepr © 2023 The Japan Society of Hepatology.…”
mentioning
confidence: 99%